THE USE OF YOUTUBE MEDIA IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Qotrunnada Nawwaroh; Istikomah Istikomah; Zetty Nurzuliana Rashed (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
The purpose of this study is to describe learning activities in this digital era that must utilize internet media with various platforms including Islamic Religious Education (PAI) learning because PAI is a compulsory subject for all types and levels of education. PAI teachers are required to have the ability to modify their learning, so that PAI material will be interesting and liked by students. The purpose of this study is to describe the use of YouTube media in PAI learning. This research is a type of qualitative research with a case study approach. Data collection techniques were conducted by interview, observation and documentation. Data analysis was conducted using Miles and Huberman's interactive analysis. The results of this study state that PAI teachers at Kartini Junior High School use YouTube a lot in their learning activities, especially when learning themes of worship that require practice, such as the theme of Hajj or Umrah, obligatory prayers, eclipse prayers, funeral prayers, and other worship services. From the measurement of students' attitudes, the results provide a lot of information and knowledge for students in PAI learning. YouTube media is not only a means of entertainment, attracting attention, and developing knowledge, but more than that it is able to provide clearer and broader information and knowledge on the topics studied. And the results of the assessment aspects in the use of YouTube media are cognitive aspects, affective aspects, and psychomotor aspects. Thus, from these assessment aspects, students have excellent thinking and reasoning skills after learning PAI material with the help of YouTube media with a score of 8.